Nickel-sodalite catalysts for hydrocracking of lloydminster atmospheric residuum. - Bergeron, Marie Colette Isabelle. (University of Ottawa (Canada), 1993)
Colour degradation and heteroatom removal were studied in hydrocracking of Lloydminster atmospheric residue using conventional CoMo/Al$\sb2$O$\sb3$ catalysts containing a Ni-sodalite component. Nickel ion exchange and impregnation were performed on basic sodalite prepared in laboratory which was combined to an aqueous mixture of $\alpha$-alumina monohydrate, ammonium paramolybdate and cobalt nitrate to form the final catalysts. Each catalyst was evaluated in a high pressure continuous flow reaction system in which hydrogen and Lloydminster atmospheric bottoms were mixed and flowed upward through a fixed bed catalytic reactor. The reaction conditions were 17.3 MPa, 415$\sp\circ$C, and 0.59h$\sp{-1}$ or 1.07h$\sp{-1}$ LSV. Ni-SOD was found to increase the rate at which the maximum colour of the diesel fraction was developed. Sulphur content of the diesel fraction was related to colour formation and a mathematical expression was developed to express colour degradation. Total nitrogen content was found to have no direct effect on colour formation. The presence of Ni-SOD also improved hydrodemetallation (HDM), hydrodesulphurization (HDS) and microcarbon residue (MCR) removal with maximum conversion for a Ni-SOD content of 10%. HDN was reduced in the total liquid product, but improved in the diesel fraction as the content of Ni-SOD increased.
Keywords: Engineering, Chemical.